Estudio de factibilidad para la creación de un centro de educación infantil en la ciudad de Latacunga, provincia de Cotopaxi. - Aldana Mantilla, Andrés Javier (2020)
The development of this project had the aims to meet the needs of many parents who work while their children are provided with a safe place where they are taken care by trained staff. And, where they also must get initial education to led to the development of their cognitive capacities, abilities, and skills, at the same time. After a needs analysis finding, it was determined that there exist an unsatisfied demand on the proper child’s attention centers. This corresponds to 1,034 children from the ages of 3 months to 5 years old in Latacunga. The parents of this children meet certain characteristics such as: age between 20 to 49 years, they civil married, others are single, or in free union, others are divorced or widowed. Most of them have children from 3 months to 5 years old. Their monthly income is over $501, and are eager to leave their children in a Childhood Education Center and pay more than $100 monthly for the services offered. The fees of these daily care centers increase a 10% every year. This rise represents the use of materials and the redesign of infrastructure, payment to teaching and administrative staff, among other expenses. Once the research was done, the feasibility to carry out this project was established. Then, the opening of a Child Education Center is viable. It will be located southern of Latacunga, city in the streets Euclides Salazar and Av. Unidad Nacional. The maximum capacity of the center will be 52 children. The Early Childhood Education Center will have qualified staff trained in early childhood education. What is more, it will provide language therapy, and kinesthetic and educational activities will be combined. Activities such as farm and children's garden, tutorial tasks, foreign language teaching will be included. The center will count on nursery teachers, an English teacher, nursery assistants, cleaning and kitchen staff, a principal and an administrator. The financial study concluded that the project demands an investment of $14,150 among fixed and deferred assets and working capital. It will have 75% of own resources and the remaining 25% will be made through a bank credit. Besides, the financial evaluation said that the NPV of the project was $16,313.35 projected at 5 years, the IRR was 37% and the Cost Benefit Ratio of 1.20, recovering the investment in the third year